Hospital admissions for lower respiratory tract infections in children born moderately/late preterm - Paula Haataja; Päivi Korhonen; Riitta Ojala; Mikko Hirvonen; Matti Korppi; Mika Gissler; Tiina Luukkaala; Outi Tammela (John Wiley and Sons Inc., 2022)
Objective: To evaluate the frequency and predictors of hospital admissions for lower respiratory tract infections (LRTIs) in moderately preterm (MP, 32+0 to 33+6 weeks) and late preterm (LP, 34+0 to 36+6 weeks) infants compared to term (T ≥37 weeks) and very preterm (VP, <32+0 weeks) infants.
Study Design: This national register‐based study covered all infants born in Finland in 1991‐2008. Data on 1 018 256 infants were analyzed in four gestational age‐based groups: VP (n = 6329), MP (n = 6796), LP (n = 39 928), and T (n = 965 203) groups. Data on hospital admissions due to bronchiolitis/bronchitis and pneumonia were collected up to the age of 7 years.
Results: Hospital admissions for LRTIs were more common in the MP and LP groups than in the T group but less frequent than in the VP group: bronchiolitis/bronchitis (VP 24.4%, MP 13.9%, LP 9.5%, and T 5.6%) and pneumonia (VP 8.8%, MP 4.5%, LP 3.3%, and T 2.4%). Compared to the term group, MP and LP birth predicted bronchiolitis/bronchitis (MP OR 1.89; 95%CI 1.75‐2.03, LP 1.51; 1.45‐1.56) and pneumonia (MP 1.49; 1.32‐1.67, LP 1.25; 1.18‐1.33) admissions. Statistically significant risk factors for LRTIs included maternal smoking, cesarean section, male sex, admission to a neonatal unit and ventilator therapy. In addition, being first‐born, being born SGA and neonatal antibiotic therapy were associated with bronchiolitis/bronchitis.
Conclusions: MP and LP births, in addition to VP birth, have a significant impact on respiratory infectious morbidity and the need of hospital admissions for LRTIs.